Towards a fairer negotiation for dynamic resource allocation in cloud by relying on trustworthiness. (2017) - Habes, Mohamed Raouf; Belleili-Souici, Habiba
The automated negotiation for resource leasing contracts in cloud produces many challenges. Since we incorporate an identity for each participant, future utilities will play a major role in their strategies in a cloud marketplace. In fact, unlike traditional agents' strategies, our strategies had to take into account two additional components, namely, future utilities involving the reputation of agents' identities as well as transactions' fees in a marketplace destined for dynamic resource allocation for cloud computing. The aim of this paper is to design such strategies that prevent any practice that may cause unfairness to arise due to some drawbacks in the resource allocation protocol helping some participants to take unfair advantages over others. Comparative experiments with non-trust model show the effectiveness of our approach in terms of fairness and social welfare.